A Short Review on Self‐Healing Thermoplastic Polyurethanes. Issue 8 (20th March 2021) - Yao, Yuan; Xiao, Meng; Liu, Wenguang
Abstract: Thermoplastic polyurethane (TPU) is a melt‐processing polymer with a high elasticity, high tensile strength, low‐temperature resistance, wear‐resistance, and corrosion resistance ability. TPU can be used in the automotive industry, electronics, medical supplies, coatings, and sports equipment. Introduction of self‐healing performance has made a considerable contribution to the service life and recyclability of TPU. The present article analyzes recent progress in self‐healing supramolecular TPUs. In particular, the importance of self‐healing mechanisms governed by covalent bonds and non‐covalent interactions in polymer design that allows for balancing mechanical performance and repairability is summarized. The critical issues and challenges associated with self‐healing supramolecular TPUs are also discussed. Abstract : Self‐healing thermoplastic polyurethanes have attracted considerable attention due to their recyclability and huge implications for the reduction of environmental burden. In this short overview, self‐healing mechanisms are summarized and the critical issues and challenges are discussed.